Titanium doped niobium oxide for stable pseduocapacitive lithium ion storage and its application for 3 V non-aqueous supercapacitor - Wang, Xu (2020)
Developing high energy density supercapacitor is of great importance to the transportation, consumer electronics and micro-grid energy storage sectors. In this contribution, we introduce a titanium doping strategy to enhance the electrochemical performance of orthorhombic phase niobium oxide (T- Nb2O5). The Ti doping is able to provide additional redox reaction and reduce the charge transfer resistance during the electrochemical reaction. As a result, Ti doped TNb2O5 shows pseduocapacitive Li+ storage capacity of 204.3 mAh g-1 and capacity retention of 88.8 % after 1000 cycles at 5C rate. Moreover, a non-aqueous supercapacitor protype based on Ti doped T-Nb2O5 and polyaniline-single wall carbon nanotube are fabricated. The 3 V prototype supercapacitor achieves an enhanced energy density of 110.3 Wh kg-1 at 150 W kg-1.